MELIHAT PERLUNYA PEMERINTAH MELAKUKAN PROGRAM REVALUASI ASET BARANG MILIK NEGARA - Yuniarto, Agung (Politeknik Keuangan Negara STAN, 2020)
ABSTRACTThe Revaluation of State Assets (BMN) asset program is a revaluation of assets that belong to the state, the purpose is to increase the validity of the value of BMN in the central government balance sheet, to become the underlying assets for the issuance of State Sharia Securities (SBSN), as well as building a BMN database better. The object of revaluation is fixed assets in the form of land, buildings and buildings, roads, irrigation and networks. This study explains and analyzes the problems of implementing the BMN Asset Revaluation in Indonesia. The results of this study are the government's initial efforts to improve the administration and fair value of BMN in the form of fixed assets, then presented in the central government's financial balance sheet to improve the quality of the central government's financial statements (LKPP). But this decision to revaluate is contrary to the Financial Accounting Standards and Government Accounting Standards (SAK / SAP), which adhere to asset valuations based on acquisition costs or exchange rates. However, it was concluded that the Government Accounting Standards Committee (KSAP) letter. support reporting the results of the 2017 fixed assets revaluation into LKPP, and revaluation by the government is indeed needed.Â ABSTRAKProgram Revaluasi aset Barang Milik Negara (BMN) adalah penilaian kembali aset-aset yang menjadi milik negara, tujuannya adalah meningkatkan validitas nilai BMN pada dalam laporan keuangan pemerintah pusat, sebagai underlying aset dalam penerbitan Surat Berharga Syariah Negara (SBSN), sekaligus pembentukan data base BMN yang lebih baik. Objek yang dilakukan revaluasi adalah berupa aset tetap Tanah, Bangunan, Jaringan, Jalan, dan Irigasi. Studi ini menganalisa serta menjelaskan permasalahan pelaksanaan Revaluasi Aset BMN di Indonesia. Dari hasil studi ini menjadi kerja keras pemerintah untuk memperbaiki nilai wajarÂ dan penatausahaan atas BMN aset tetap, yang disajikan dalam laporan keuangan pemerintah pusat dalam meningkatkan kualitas laporan keuangan pemerintah pusat (LKPP). Tetapi keputusan melakukan revaluasi ini bertentangan dengan Standar Akuntan Keuangan dan Standar Akuntansi Pemerintah (SAK/SAP), dimana menganut penilaian aset berdasarkan harga perolehan atau harga pertukaran. Akan tetapi telah disimpulkan bahwa surat Komite Standar Akuntansi Pemerintah (KSAP). mendukung pelaporan hasil revaluasi aset tetap 2017 kedalam LKPP, dan revaluasi yang dilakukan pemerintah memang diperlukan.Â